Numerical analysis on the thermal load and NO emission of a novel 1 MW pyrolysis gas/natural gas-fired industrial burner - Dávid Csemány; Dániel Füzesi; Viktor Józsa (Results in Engineering, 2025)
Climate neutrality mandates efficient waste management and the energy use of non-reusable and non-recyclable waste types. Even though the potential in this field is in the range of 1 % of the energy needs, it is a critical step towards a sustainable economy. Pyrolysis is an emerging solution that provides coke, oil, and gas in various shares, depending on the feedstock. The first two products can be processed and utilized by various industries, while local gas use is the most rational solution. For this purpose, a novel burner was designed to run on natural and unfiltered pyrolysis gas to allow startup and dynamic, flexible operation since the currently installed burner failed to meet the emission limitations for long-term use. The complete combustion chamber and its inlets were provided, and the heat release pattern and pollutant emissions at partial and full load were numerically analyzed at a 1:5 turndown ratio, a typical requirement for boilers. It was concluded that there is no need for the tertiary air inlet if a fully premixed burner is used. The secondary air is sufficient to keep the NOx emission and the flame temperature at sufficiently low values, meeting the 250 mg/Nm3 emission standard at 3 % flue gas O2 level and the 1400 °C refractory wall requirements, respectively. The heat release pattern and flow characteristics of pyrolysis gas were similar to that of natural gas at all loads, both properly occupying the combustion chamber, implying that the novel dual-fuel burner concept was adequately designed for this application.